2023
DOI: 10.1021/acscatal.3c01448
|View full text |Cite
|
Sign up to set email alerts
|

Surface Ir+5 Formation as a Universal Prerequisite for O2 Evolution on Ir Oxides

Abstract: The large-scale deployment of polymer electrolyte water electrolysis (PEWE) is largely limited by the use of O 2 evolution reaction (OER) catalysts based on scarce and expensive iridium in PEWE anodes. The ensuing need for betterperforming, Ir-based OER catalysts requires an improved understanding of the relation between these materials' activity and their physicochemical operando properties. To shed light on this matter, here, we employed operando modulation excitation X-ray absorption spectroscopy to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 72 publications
2
6
0
Order By: Relevance
“…At potentials >1.4 V RHE , the Ir oxidation state begins to plateau, with the oxidation state being higher in alkaline electrolytes compared to acid. Prior work has suggested the presence of higher oxidation states of iridium at this potential region; , however, recent reports also suggest that the redox transitions at a high potential correspond, in part, to the formation of holes on surface oxo groups. ,, The trends observed in the XANES spectra are also consistent with the shortening of the Ir–O bond with increasing potential, as observed in the X-ray absorption fine structure (EXAFS). The Fourier transforms of EXAFS spectra and the simulations of the spectra (Figures S14–S15 and Table S2) revealed the presence of characteristic Ir–O bond distances and very weak Ir–Ir interaction peaks, showing a short-range disorder structure of amorphous IrO x .…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…At potentials >1.4 V RHE , the Ir oxidation state begins to plateau, with the oxidation state being higher in alkaline electrolytes compared to acid. Prior work has suggested the presence of higher oxidation states of iridium at this potential region; , however, recent reports also suggest that the redox transitions at a high potential correspond, in part, to the formation of holes on surface oxo groups. ,, The trends observed in the XANES spectra are also consistent with the shortening of the Ir–O bond with increasing potential, as observed in the X-ray absorption fine structure (EXAFS). The Fourier transforms of EXAFS spectra and the simulations of the spectra (Figures S14–S15 and Table S2) revealed the presence of characteristic Ir–O bond distances and very weak Ir–Ir interaction peaks, showing a short-range disorder structure of amorphous IrO x .…”
Section: Resultssupporting
confidence: 59%
“…Combining the operando XANES with our previous DFT calculations, 42 oxidation state being higher in alkaline electrolytes compared to acid. Prior work has suggested the presence of higher oxidation states of iridium at this potential region; 46,47 however, recent reports also suggest that the redox transitions at a high potential correspond, in part, to the formation of holes on surface oxo groups. 35,48,49 The trends observed in the XANES spectra are also consistent with the shortening of the Ir−O bond with increasing potential, as observed in the X-ray absorption fine structure (EXAFS).…”
Section: Resultsmentioning
confidence: 86%
“…63,409−412 Also, operando Ir L-edge experiments indicate much lower redox activity of crystalline oxides, 413 basically mimicking their reduced pseudocapacitance. 414 Similarly, effective charge accumulation with amorphous IrO x was also evidenced by in situ evanescent wave spectroscopy. 415 Some controversy surrounds Ir L 3 -edge experiments that suggest iridium reduction under OER potentials.…”
Section: Mechanistic Details Over Ir-based Materials and Active Phase...mentioning
confidence: 83%
“…To date, operando studies of the electronic structure of Ir‐based OER catalysts have focused on X‐ray photoelectron spectroscopy (XPS) and X‐ray absorption spectroscopy (XAS) respectively. [ 10,19,20–22,24–32 ] Such studies have shown Ir oxidation states as high as Ir V may be reached [ 10,26,28,30 ] during the OER. Moreover, XAS at the O K‐edge has shown that at these high oxidation states, a variety of electron‐deficient oxygen species form, including bridging µ 2 ‐O bound to two iridium atoms and the terminal µ 1 ‐O species bound to a single iridium atom.…”
Section: Introductionmentioning
confidence: 99%